"Upside down" reversal of vision after third ventriculostomy - (:unkn) unknown (My University, 1990)
Upside-down reversal of vision is a very rare kind of visual illusion characterized by the upside-down appearance of all objects within the visual field. Only seven cases have been reported since its description. In this paper, we report a case of upside-down reversal of vision, which occurred following a third ventriculostomy operation for hydrocephalus. This is the first case reported in the literature after a surgical intervention.
Keywords: Humans; Adolescent; Male; Hydrocephalus; Optical Illusions; Ventriculostomy; Vision Disorders